Occupational stress as a risk factor for cardiovascular accidents in medical staff of anesthesiology and intensive care units (review) - V. E. Ironosov; D. O. Ivanov; K. V. Pshenisnov; Yu. S. Aleksandrovich; A. V. Agafoniva (Вестник анестезиологии и реаниматологии, 2025)
Introduction. Occupational stress is one of the most common causes of cardiovascular catastrophe among emergency response personnel.The objective was to analyze the literature sources on assessing the level of stress and its impact on health indicators in medical staff of anesthesiology and intensive care units.Materials and methods. The analysis included 70 publications from the PubMed and e-library abstract databases for the period from 2017 to 2023. The search was carried out using keywords: professional burnout syndrome, stress, personality, anesthesiologist-resuscitator, intensive care unit, heart rate variability, provider burnout syndrome, stress, personality, anesthesiologist, intensive care physician, intensive care unit, heart rhythm variability. After a primary examination of abstracts, 20 articles were excluded from the review as there was a lack of access to the full text or they were devoted to organizational prevention activitiesResults. It has been demonstrated that a long working day for more than 10 years is associated with an increase in the likelihood of developing coronary heart disease (CHD), especially among men. A linear increase in the risk of recurrent CHD attacks was established in a working time of more than 40 hours a week for four years after a myocardial infarction. It was revealed that severe occupational stress was associated with a decrease in HRV due to parasympathetic influences. In resident anesthesiologists, the maximum inhibition of heart rhythm variability was noted at the stage of induction of anesthesia and on the eve of night watch.Conclusion. A long-term increase in sympathetic activity of the autonomic nervous system and suppression of parasympathetic impulses indicate a high probability of developing cardiovascular diseases associated with the level of occupational stress.